2015
DOI: 10.4314/ajtcam.v13i3.18
|View full text |Cite
|
Sign up to set email alerts
|

Traditional, complementary and alternative medicine use of chronic disease patients in a community population in Myanmar

Abstract: Background: The aim of this study was to assess the prevalence and associated factors of Traditional, Complementary and Alternative Medicine's (TCAM) use of chronic disease patients in a community setting in Myanmar. Materials and Methods: A cross-sectional community survey was conducted in the Kyauk Tan Township with the International Complementary and Alternative Medicine Questionnaire (I-CAM-Q). Results: Of the 1600 participants in the survey, the overall prevalence of any TCAM use (providers, products or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…In agreement with some previous studies [4,[25][26][27][28][29][30][31], this study found that in unadjusted analysis older age (≥60 years) was associated with AYUSH and THP utilization. Several studies showed that female sex was associated with TCM provider use [4,25,30], which in this study was found for AYUSH utilization but not for traditional health practitioner utilization.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with some previous studies [4,[25][26][27][28][29][30][31], this study found that in unadjusted analysis older age (≥60 years) was associated with AYUSH and THP utilization. Several studies showed that female sex was associated with TCM provider use [4,25,30], which in this study was found for AYUSH utilization but not for traditional health practitioner utilization.…”
Section: Discussionsupporting
confidence: 93%
“…While in a previous surveys [1,4], compared to scheduled tribes, all other castes were less likely utilizing AYUSH. Most previous studies [25][26][27][28] found an association between rural residence and TCM use, which is con rmed in this study for both AYUSH and THP utilization. Reasons for this may be attributed to subsidized public health care mostly serving economically better-off urban dwellers, while rural public health care is poorly staffed and has poorer quality, increasing the dependency on private providers, such as AYUSH and THP, for health care [4].…”
Section: Discussionsupporting
confidence: 87%
“…The overall prevalence of any TCAM (Traditional Complementary and Alternative Medicine) use in a community population in Myanmar was 95.1% (Peltzer, Win-Myint-Oo & Pengpid, 2016). With the prevalence of more than 10%, diabetes needs a special attention including the psycho-social management and the major challenges in Myanmar are public health seeking behavioral issues, presence of traditional medicine, lifestyle and diet and issues pertaining to religion (Than-Than-Aye, Moe-Wint-Aung & Ei-Sandar-Oo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While these are both valuable contributions to the literature, there is a distinctive lack of research using the CAF to understand 'lay' knowledge of health and treatment. Peltzer et al (2016) investigated the use of traditional medicine used by chronic disease patients in Myanmar; contrastingly, Khaing et al (2015); Risso-Gill et al (2013); Sommanustweechai et al (2016) and Zaw et al (2015) analysed Myanmar's health system and the disparities within it while maintaining a focus on biomedicine.…”
Section: Introductionmentioning
confidence: 99%